Where to locate new industrial sites in case of land shortage? A nationwide analysis of regional development plans with particular regard to the conception of “Regionale Kooperationsstandorte” in the Ruhr Metropolis - Iwer, Nicole; Gerber, Markus (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Due to increasing density-dependent competitions in land use, it is difficult to plan new industrial areas, especially for factories and businesses with a need for large-scaled sites. Economic interest groups demand to plan new industrial areas to keep the region in a competitive position. At the same time, many citizens and local politicians are concerned about new specific land use areas for industries. To locate suitable industrial sites in the catchment area of municipalities with land shortage and a high demand for space and to involve regional stakeholders into the planning process, new regional planning tools are required. The case study about the “Regionale Kooperationsstandorte” planning tool in this paper shows which additional values and challenges the recipients of the plan expect from the new planning approach. Apparently, the new regional planning tool is generally accepted by most of the stakeholders in the Ruhr Metropolis. But specific regulations and particular sites are highly controversial, due to diverging interests of different stakeholders and municipalities or due to changing circumstances, so that it is not possible to reach a consensus on all issues.